MENYULAM MASA DEPAN LEWAT BENANG BUDAYA SULAMAN SONGKET KAPALO KOTO SEBAGAI WARISAN DAN POTENSI MASA DEPAN - Yonanda, Hirva; Wilis, Ratna; Amalina, Khairani; Arianto; Azzahra, Assyfa; Rahman, Abdul; Rahimatul Wardanil, Zaura; Muslimah, Afiatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Kapalo Koto Songket Embroidery is a cultural heritage rich in aesthetic and local identity values. However, modernization and lack of regeneration threaten its continuity. This research aims to explore the role of this embroidery as both heritage and future potential. A qualitative method was used with in-depth interviews involving local artisans and cultural figures in Kapalo Koto. The findings reveal that songket embroidery holds not only high economic and artistic value but also serves as a symbol of identity and community pride. Nevertheless, the lack of interest among the younger generation and limited digital marketing are major challenges. The study concludes that preserving Kapalo Koto songket embroidery requires collaboration among cultural actors, the government, and technological support to develop it as a sustainable creative economic asset for the future.